(untitled) (Comillas Journal of International Relations, 2020)
In 1956 three motion pictures, based upon novels written by Shintaro Ishihara, were released in Japan. Its success will stimulate the production of new films, forerunners of the so called Nuberu Bagu: a young national cinema oriented to the radical transformation of the Japanese films and society. The new filmmakers were very critic with his time and country, and they were the basis of an avant-garde film movement in Japan. The most distinguished member of this group was Nagisa Oshima, the author of emblematic films as Cruel Story of Youth (1960). All these young filmmakers will share a common interest for the formal exploration towards the renovation of film language, as they tried to practice a radical and revolutionary cinema, a new way of understanding their country, with the final purpose to renew the cultural and cinematographic patterns in Japan.